O discurso de organizações supranacionais sobre a economia informal - Cardoso e Silva, Alexandre Dias (2018)
The informal economy accounts for a large part of the global economic movement, and according to some studies such as Schneider and Williams (2013) and Williams (2015), could account for about 40% of the global economic movement. Considering the current and historical context of the informal economy, its multiple causalities and manifestations, factors that impact and increase informality, the research problematic lies in the perspective of unveiling the discourses that circumscribe the field of study defined by the informal economy. In this study, it is important to unveil the conceptions of supranational and global discursive structures (the World Trade Organization / WTO, International Labor Organization / ILO and the World Bank) on the informal economy and how they articulate, contradict, converge and diverge to the issue of informality. To do so, the critical discourse approach will be used in an attempt to unravel contradictions and distortions that the discourse of these organizations carry on the theme. The research will be based on the methodological tools provided by the Critical Discourse Analysis – CDA, of English matrix, proposed by Fairclough (2001). This study is qualitative in nature, based on documentary research in publications, specific reports and manifestations of supranational organizations WTO, ILO and World Bank. Data analysis will follow the Fairclough CDA strategy (2001) from the dimensions and categories of analysis proposed by the method CDA. The results of the research point to a situation of complementarity and articulation between discourses that converge in relation to the phenomenon of informality in the world, as well as indicates discursive constructions under the same ideological basis for all organizations.